Target lipidomics approach to reveal the resolution of inflammation induced by Chinese medicine combination in Liu-Shen-Wan against realgar overexposure to rats. (1st March 2020) - Wang, Jiaojiao; Ding, Lanfang; Zhou, Jing; Ma, Hongyue; Wu, Yuanyuan; Wang, Jiajia; Lv, Xiang; Liu, Shengjin; Wang, Hengbin; Yan, Yanqing; Luo, Niancui; Li, Quan; et al.
Abstract: Ethnopharmacological relevance: Liu-Shen-Wan (LSW) is one of the popular over-the-counter drugs in Asia, which contains realgar (As4 S4 ), used for the treatment of upper respiratory tract inflammation and skin infections. However, the safety and potential risk of this arsenic remain unknown. Aim of the study: The aim of this study was to determine total arsenic in tissue and investigate effects of regular dose and overdose LSW exposure on rat liver. Materials and methods: We used a target lipidomics approach to quantify inflammatory eicosanoids and employed ICP-MS to determine total arsenic in tissue. Results: The results showed that oral administration of 8 and 40 mg/kg LSW (1 and 5 fold human-equivalent dose) induced light changes of liver lipidomic profile in rats, which was associated with anti-inflammatory function of LSW. In our recent report, we observed that 41 and 134 mg/kg realgar (40 and 132 fold human-equivalent dose) stimulated rat liver inflammation through up-regulation of pro-inflammatory LOX-derived, CYP-derived HETEs and COX-derived PGs. However, we found that LSW in the form of drug combination, containing 41 and 134 mg/kg realger, could not stimulate these similar inflammatory responses in rats, although the liver total arsenic levels of the realger and LSW groups were same. Conclusion: The downregulation of pro-inflammatory response showed that the LSW containing realger is safer than realger alone administrated to rats. These results suggested that Chinese medicines combination could reduce realgar-derived arsenic toxicity in rats. Graphical abstract: Image 1